Realization of Acoustic Method of Colorado Beetle Elimination - Sokol , Galyna Ivanovna; Molnar , Taras Stepanovich; Sokol , Andrey Vladymyrovich (Fundamental Research and Application of Physical Science Vol. 9, 2023)
The purpose of the study is the mechanical characteristics of a living body. The article examines the specifics of the impact of acoustic waves on the organisms of living beings. It is commonly known that vibrations and acoustic oscillations can cause both negative and positive influence on living organisms. The most harmful effect is caused by the tone acoustic oscillations when the tone frequency coincides with the resonance frequency of the whole body or individual organs. It is understood that such resonance frequencies of human organs fall between 0.5 and 20 Hz. Only in this situation, when a person is in an acoustic field with a frequency that is not the same as their resonance frequency, can the human body be shielded from harmful acoustic waves. On the contrary, we can use the effect of acoustic fields on the organisms of plant pests with a frequency corresponding to the resonant frequency of the pest's body. Then the acoustic field will have a destructive effect on the plant pest. The death of the Colorado beetle under the influence of vibrations and acoustic vibrations was discovered in the laboratory. It is necessary to note slackness of the beetles subjected to acoustic influence in a mode of radiation of monochromatic waves. Any influence of acoustic waves on a potato at direct survey, and also after time till the harvesting moment had not been revealed. The method and device for its implementation are developed and described below. The author registered in the Patent Office of Ukraine "Acoustic solution of the Colorado beetle and device for implementation" No. 25548 A 01 M 1/04, 1/18 October 30, 1998. Destruction of the Colorado beetle by affecting its body with acoustic vibrations. in accordance with the reduction of labor intensity of the operation with increased toxicity. The results of this work are of great importance in the study of the relationship between the processes in the atmosphere of the Earth and the biosphere through acoustic vibrations.